Commiphora leptophloeos Phytochemical and Antimicrobial Characterization - de Souza Pereira, Jorge J.; Pereira, Aline de P. C.; Jandú, Jannyson J. B.; da Paz, Josinete A.; Crovella, Sergio; dos Santos Correia, Maria T.; de Azevêdo Silva, Jaqueline (Frontiers in Microbiology, 2017)
Commiphora leptophloeos is usually known for its medicinal purposes from local communities in Northeast Brazil. The qualitative phytochemical analysis by TLC of C. leptophloeos extracts detected the presence of phenolic compounds, flavonoids and reducing sugars. H1NMR analysis revealed the presence of hinokinin, a bioactive lignan characterized in this article. The phenolic compounds were identified by HPLC and three were described: Gallic, Chlorogenic and Protocatechuic acids. The MIC values of hinokinin ranged from 0.0485 to 3.125 mg/mL in different S. aureus clinical isolates, and showed a bactericidal activity against MRSA isolated from blood (MMC 0.40 mg/mL) and postoperative secretion (MMC = 3.125 mg/mL). C. leptophloeos extracts showed antimicrobial activity against Mycobacterium species such as M. smegmatis (MIC = 12.5 mg/mL) and M. tuberculosis (MIC = 52 mg/mL). Herein we also determined C. leptophloeos toxicity by HC50 tests in vitro with hemolytic activity detected of 313±0.5 µg/mL. The present findings showed that C. leptophloeos possesses inhibitory properties against MRSA as well as various Gram-positives, Gram-negatives and Fungi microorganisms, and should also be investigated for its potential against Mycobacterium. Furthermore, we have identified for the first time the presence of hinokinin in Commiphora genus.